Answer:
(r o q)(-1) = 20
(q o r)(-1) = -11
Explanation:
Given
![q(x) = -2x + 1](https://img.qammunity.org/2021/formulas/mathematics/college/ojyct4cdkkon381midas8x6knidyei95zz.png)
![r(x) = 2x^2 + 2](https://img.qammunity.org/2021/formulas/mathematics/college/gzn3xtcgo8vfp7ssy314fb7c9ytbmh7si6.png)
Solving (a): (r o q)(-1)
In function:
(r o q)(x) = r(q(x))
So, first we calculate q(-1)
![q(x) = -2x + 1](https://img.qammunity.org/2021/formulas/mathematics/college/ojyct4cdkkon381midas8x6knidyei95zz.png)
![q(-1) = -2(-1) + 1](https://img.qammunity.org/2021/formulas/mathematics/college/krp48nsmdjgv1wxo9xx7b0tax763sn9ter.png)
![q(-1) = 2 + 1](https://img.qammunity.org/2021/formulas/mathematics/college/oedhmz3qm8e8ke7t4notggsxsl1it3rj8r.png)
![q(-1) = 3](https://img.qammunity.org/2021/formulas/mathematics/college/sdkoc3uah4t2sgv4ksydkr3jnxybiu7w08.png)
Next, we calculate r(q(-1))
Substitute 3 for q(-1)in r(q(-1))
r(q(-1)) = r(3)
This gives:
![r(x) = 2x^2 + 2](https://img.qammunity.org/2021/formulas/mathematics/college/gzn3xtcgo8vfp7ssy314fb7c9ytbmh7si6.png)
![r(3) = 2(3)^2 + 2](https://img.qammunity.org/2021/formulas/mathematics/college/unbvnw1t0a18kurzh7lm5b5rrecmp7l4fg.png)
![r(-1) = 2*9 + 2](https://img.qammunity.org/2021/formulas/mathematics/college/y5cp3f7myhfaqu8acwix6k3aooxym30ggp.png)
![r(-1) = 20](https://img.qammunity.org/2021/formulas/mathematics/college/yu3vx4nx0xxrzloyidmjb4rhh19ku8g9hd.png)
Hence:
(r o q)(-1) = 20
Solving (b): (q o r)(-1)
So, first we calculate r(-1)
![r(x) = 2x^2 + 2](https://img.qammunity.org/2021/formulas/mathematics/college/gzn3xtcgo8vfp7ssy314fb7c9ytbmh7si6.png)
![r(-1) = 2(-1)^2 + 2](https://img.qammunity.org/2021/formulas/mathematics/college/dravtwfmhghhfxldly0qija7gtgy6ebysa.png)
![r(-1) = 2*1 + 2](https://img.qammunity.org/2021/formulas/mathematics/college/f4vq3uep30jtoxzthrttd0ucmuggalghqx.png)
![r(-1) = 6\\](https://img.qammunity.org/2021/formulas/mathematics/college/lriprggcn3e677yr2xaor1n2yyh7rjyql6.png)
Next, we calculate r(q(-1))
Substitute 6 for r(-1)in q(r(-1))
q(r(-1)) = q(6)
![q(x) = -2x + 1](https://img.qammunity.org/2021/formulas/mathematics/college/ojyct4cdkkon381midas8x6knidyei95zz.png)
![q(6) = -2(6) + 1](https://img.qammunity.org/2021/formulas/mathematics/college/riaz05p3z87bjh2zks3gtfvxp1siahao0m.png)
![q(6) =- 12 + 1](https://img.qammunity.org/2021/formulas/mathematics/college/fxlthmntbk9u6xhq0ix1543vd5vmldstv2.png)
![q(6) = -11](https://img.qammunity.org/2021/formulas/mathematics/college/kodk7siaqulbxfxgtfo7jityhgn41ux0rs.png)
Hence:
(q o r)(-1) = -11